Article PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Saka Perwira Hadi; Sulastri Irbayuni (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Human resources are needed by companies to realize organizational goals. To make it happen, companies need to pay attention to the work environment and work discipline so that employee performance can be maximized. The purpose of this study was to determine the effect of work environment and work discipline on employee performance at CV Cahyo Utomo Kubah Nganjuk. The method used is a quantitative method and data collection using a questionnaire with a Likert scale as a measuring tool. The population and sample used are employees of the production division at CV Cahyo Utomo Dome with a total of 35 employees. The data used are primary data and secondary data using Partial Least Square (PLS) analysis. Based on the results of research that has been done: 1). A well-managed work environment can also have a good influence on employee performance at CV Cahyo Utomo Dome Nganjuk. 2). Good discipline has a good influence on the performance of employees of CV Cahyo Utomo, Nganjuk. Keywords: Work Environment, Work Discipline, Employee Performance.